Fransjohan Pretorius, The A to Z of the Anglo-Boer War: A welcome and reliable companion for students and scholars (Historia, 2021)
Scarecrow Press are to be congratulated for bringing out so quickly an affordable paperback edition of this volume, which will surely become a standard work of reference, a welcome and reliable companion for scholars and students alike who are working on the Anglo-Boer War. The book is a superb piece of research, scholarship, and clearly the product of many years of careful labour, reflection, and precise exposition. Embellished with maps and a chronology, it has a useful introduction and overview of the origins and course of the war, and contains over 600 cross-referenced entries, covering nearly every conceivable facet of significance in the war. The bibliography, beginning with a scholarly six-page review essay, spans 58 pages and must be the most up-to-date bibliographic source available.